DEATH AND REPRESENTATION IN THE CINEMA OF ALBERT SERRA - Trueba Mira, Virginia (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
On the occasion of the film by Albert Serra, The Death of Luis XIV(2016), this work intends to think the outside of representation, understood in the sense it has in some postmetaphysical thinkers —Foucault, Deleuze, Blanchot— as that of which no order of similarity can take charge because it constitutes a radical otherness. That otherness is, in a maximun degree, that of death. Now, Serra’s film gets strained at the moment where death stops being seen because it gets hidden behind representational systems that, in this case, are of two types: the courtier, and the medico-clinical. It is this type of blindness that Serra’s cinema puts on the stage.